CITY BRANDING KOTA SOLO MELALUI SAYUR LODEH - Eka Surya Herlita; Rini Darmastuti; Dian Novita Kristiyani (Fakultas Dakwah dan Komunikasi, 2021)
Cultural identity can be used to increase city branding, this is also applied in Solo. The identity of Solo is shown through culture, which is traditional cuisine named “sayur lodeh”. This cuisine has been believed to be ‘tolak bala’ (preventing distress) during ‘pageblug’ period. This paper discusses two common researches which are qualitative and ethnography. The result of this research are: First, sayur lodeh is a cultural symbol which has meaning of togetherness when we face Covid-19 virus. Second, to suggest people to cook sayur lodeh during the pandemic is one of communication strategy to convey health protocol through symbold that presented from each component of sayur lodeh. Third,the cultural identity of Solo can be built by their cultural heritage, including using sayur lodeh.